2018
DOI: 10.1128/iai.00356-18
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Articular and Systemic Inflammation by Kava-241 in a Porphyromonas gingivalis-Induced Arthritis Murine Model

Abstract: Rheumatoid arthritis (RA) is an inflammatory disease that has been linked to several risk factors, including periodontitis. Identification of new anti-inflammatory compounds to treat arthritis is needed. We had previously demonstrated the beneficial effect of Kava-241, a kavain-derived compound, in the management of -induced periodontitis. The present study evaluated systemic and articular effects of Kava-241 in an infective arthritis murine model triggered by bacterial inoculation and primed with a collagen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…gingivalis was previously demonstrated as a specific TLR4-dependent endothelial actor in pro-inflammatory TNF-α and IL-6 secretion following endothelial invasion or via its virulence factors such as LPS 55,56 . Moreover, several studies demonstrated the importance of NF-K B pathways in P. gingivalis elicited inflammation in several cell types [57][58][59][60] . In a previous report, we were able to demonstrate that TLR4 + MV generated by Pseudomonas were true mediators of NF-K B-dependent signaling in TLR4 − HEK engineered cells via I K B phosphorylation 61 .…”
Section: Discussionmentioning
confidence: 99%
“…gingivalis was previously demonstrated as a specific TLR4-dependent endothelial actor in pro-inflammatory TNF-α and IL-6 secretion following endothelial invasion or via its virulence factors such as LPS 55,56 . Moreover, several studies demonstrated the importance of NF-K B pathways in P. gingivalis elicited inflammation in several cell types [57][58][59][60] . In a previous report, we were able to demonstrate that TLR4 + MV generated by Pseudomonas were true mediators of NF-K B-dependent signaling in TLR4 − HEK engineered cells via I K B phosphorylation 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kava-205Me improved the rate of wound healing associated with soft tissue inflammation and osteoclast activation in a model of acute P. gingivalis-induced calvarial destruction, as well as inducing a reduction in paw swelling and joint destruction. Another kavain analog, namely Kava-241, decreased the number of inflammatory cells and osteoclasts within the joints of mice exposed to P. gingivalis, as well as decreasing serum TNF-α [ 62 ]. The potential of kavalactone analogs in reducing P. gingivalis-induced TNF-α production was also shown in macrophages [ 66 ].…”
Section: Regulation Of the Inflammatory Responses By Kava And Its mentioning
confidence: 99%
“…Pathogen-free DBA1/BO male mice (Taconic Farm, Rensselaer, NY) were used in this study (Huck et al, 2018). Pathogen-free female mice with ovariectomy were not used to be consistent with prior protocols (Huck et al, 2018). Mice were fed sterile food and distilled water ad libitum .…”
Section: Methodsmentioning
confidence: 99%